Analisis Metode Balanced Scorecard Sebagai Pengukuran Kinerja Puskesmas Prambon - Awalanty, Aprilia Putri; Linawati, Linawati; Tohari, Amin (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research is in the background that a balanced scorecard is a management system used to implement strategies, evaluate performance not only from financial aspects, but also involving non-financial aspects. In addition, a balanced scorecard is used to convey the company's vision, strategy, and performance expectations. The purpose of this study is to analyze the performance of the Prambon Health Center seen using the balanced scorecard method. This research uses a descriptive quantitative approach and is conducted at the Prambon Health Center. The results of this study show that the performance of the Prambon Health Center is measured by the balanced scorecard method from a financial perspective on the economic and efficiency ratios in 2021 to 2023 showing good results, and on the effectiveness ratio seen in 2021 to 2023 showing poor results. From a customer perspective, measured using customer satisfaction from 2021 to 2023, it shows good results. From an internal business perspective measured using the ALOS indicator seen from 2021 to 2023 shows good results, The BOR indicator seen in 2021 to 2023 shows poor results, the TOI indicator seen in 2021 to 2023 shows poor results, and the BTO indicator seen in 2021 to 2023 shows good results. The conclusion from the data analysis from the Prambon Health Center measured using a balanced scorecard for the period from 2021 to 2023 is always increasing every year. In 2021 it showed quite good results, in 2022 it showed good results, and in 2023 it showed good results.